Biological activity and GC-MS determination of bioactive components of Clerodendrum viscosum (Vent.) from Siraha District, Nepal - Yadav, Shivdev; Yadav, Santosh Kumar; Subba, Bimala (Scientific World, 2024)
Clerodendrum viscosum has a long history of medical use in Asian countries with a variety of bioactivities. Although the chemical constituents of plants are strongly influenced by their surroundings, little is known about the chemical composition and biological activity of C. viscosum that is growing in Nepal's Siraha District. Therefore, the aim of this study was to evaluate the total phenolic content, flavonoid content, and biological activity, GC-MS analysis of C. viscosum leaves that was collected from the Siraha District. The methanolic extract of C. viscosum leaf was prepared and the phytochemicals were assessed, its TPC and TFC were estimated, and antioxidant and α-amylase inhibitory activities were determined following standard methods. Hexane soluble fraction of methanol extract of C. viscosum was subjected for GC-MS analysis. The TPC of the extract was found to be 197.68±0.11 mg GAE/g and its TFC was 105.14±0.026 mg QE/g. The IC50 value for DPPH free radical was found to be 26.85 0.150 g/mL, while the IC50 value for α-amylase enzyme activity was found to be 121.48 0.424 g/mL. The presence of several bioactive components was revealed by the GC-MS chromatogram, with phytol being a major constituent.